The effect of isolation on job crafting in telecommuting: Mediating effects of networking behavior and moderated mediating effects of affective commitment - Lee, SuBin; Heo, ChangGoo (Korean Journal of Industrial and Organizational Psychology, 2021)
The aims of this study was to identify what behavior of employees in order to overcome the isolation in the environment in which telecommuting was implemented. Specifically, this study was the networking behavior will appear as a positive coping method for the employees to overcome the isolation, and the mediating process that it will have a positive effect on job crafting through these behaviors is examined. Also want to identify the moderating effect according of affective commitment in this influence series of processes. For this purpose, an online survey was conducted on employees who are currently telecommuting from domestic companies and a total of 313 data were analyzed. The results of this study are as follows. First, professional isolation had a positive related on task networking behavior and social isolation had a positive related on friendship networking behavior. Second, the relationship between networking behavior and job crafting had all positively related. Third, the mediating effect of networking behavior was significant in the relationship between isolation and job crafting. Fourth, the moderating effect of affective commitment was significant only in the relationship between social isolation and friendship networking behavior. Fifth, the moderated mediating effect of affective commitment was significant only in the indirect effect of friendship networking behavior. Based on these findings, we expect to help to understand the emotions and behaviors of employees that may appear at the beginning of introduction of telecommuting in depth.